Saberes docentes, avaliação e inclusão: estudo de uma realidade - Caramão, Márcia Terra Marques (2009)
This research is inserted in the Research Area of Special Education of the Pos Graduation Program in Education from the Universidade Federal de Santa Maria. Proposes a reflection on the Teachers Knowledge and the Evaluation of Students with Special Educational Needs Included in the Public Teaching System, in order to search participation in an active way in the production of knowledge from teachers through study meetings about the Evaluation, proposing ways which point at the possible answers to the difficulties and worries that the evaluation process causes. The objectives which form the basis to this research were to investigate how the learning evaluation of students with special educational needs is processed and which teachers knowledge is involved in these pedagogical practices. For the production of this research the following themes were used: teachers knowledge, evaluation, inclusion and the evaluation of students with special educational needs. This research is one of the cooperative critical of research-action kind with qualitative approach. The data collection happened with the participation of eight teachers of the beginning years of the elementary teaching of a school from the public teaching system from a city of the Northwest region of Rio Grande do Sul, which participated in a focal group. During the teachers work group, reflections, readings, debates, opinions and suggestions about evaluation of the school learning in the beginning years of the elementary teaching with the students with special educational needs were motivated. Still to complement the data collection teachers notes were used, in which were registered each particular point of the meetings and at the end, a questionnaire with seven open questions for the teachers involving concepts and important aspects about evaluation, teachers knowledge and inclusion. The answers were treated by content analysis and revealed the practice of each teacher regarding the evaluation made with the students with special educational needs, as well as the knowledge that each teacher uses in their evaluation practice, be it planned or not. This research made it possible a contact among the teacher of the group with greater frequency, an exchange of experiences that proposes reflections on the students with special educational needs and the evaluation as a significant process to the school progress. The evaluation was regarded as a challenge which is present in the school routine and in the teachers planning as a principal part for the development of significant work, and they reported verbally as a process which generates nervousness and anxiety, and it has been noticed that they feel difficulties producing the evaluation for all the students and mainly for those who present special educational needs. The teachers still revealed restrict school evaluation knowledge and their main theories. The evaluation procedures described by the teachers as the most used are: the research in the pedagogical books, the work in groups, the pedagogical games and the oral and written work. It is possible to notice that they use a daily planning to exert their activities with the students. It has been evident during the research the difficulty that the teachers feel when evaluating the students with special educational needs as well as all the students. The studies in Evaluation and School Inclusion need to be themes among the teachers all the time.